Tower in the sky - Hiwot Teffera (Ethiopia : Addis Ababa university press, 2012)
"An eighteen-year old girl sets out to meet a young man whom she had never met before and is swept away by a series of events that transformed her life in a way she could have never imagined."--Back cover.
Keywords: 1974; Ethiopia -- History -- Revolution, 1974 -- Personal narratives; Ethiopia..; History..; Personal narratives..